Community Participation in the Belitung Aspiration and Complaint Channel (BESADU) Program in Realizing Smart Governance in West Belitung Regency - Isnaini, Sarifah; Murodi, Ahmad; Muhtadi, Yudi (Program Studi Ilmu Administrasi Negara FISIP UMRAH, 2025)
Community participation plays a vital role in determining the success of government programs and development planning, particularly in regions implementing smart city policies such as West Belitung Regency. Smart Governance, as one of the main dimensions of Smart City, aims to enhance the quality, transparency, and efficiency of public administration. This study focuses on the Belitung Aspiration and Complaint Channel (BESADU) Program an innovative initiative designed by the Regent and Deputy Regent of West Belitung to collect and respond to public aspirations and complaints regarding public services, bureaucratic management, and policy implementation. The objective of this study is to analyze the level and form of community participation in the BESADU program as an effort to realize Smart Governance. Using a qualitative descriptive method, data were collected through interviews, observation, documentation, and triangulation of data sources involving ten community respondents. The results indicate that community participation in the BESADU program is reflected in four indicators: intensive communication, conducive socio-economic-political-cultural climate, opportunities for participation, and freedom of creativity and initiative. The findings show that while the program has improved public service responsiveness and citizen engagement, there remain challenges such as the lack of system integration in complaint monitoring and uneven follow-up by local government units. The study concludes that by utilizing technology and fostering direct and digital-based socialization, the BESADU program has contributed significantly to building a transparent, responsive, and collaborative governance system aligned with the principles of Smart Governance in West Belitung Regency.